Condensation-Based Methods for the C–H Bond Functionalization of Amines - Chen, Weijie; Seidel, Daniel (Synthesis, 2021)
This review aims to provide a comprehensive overview of condensation-based methods for the C–H bond functionalization of amines that feature azomethine ylides as key intermediates. These transformations are typically redox-neutral and share common attributes with classic name reactions such as the Strecker, Mannich, Friedel–Crafts, Pictet–Spengler, and Kabachnik–Fields reactions, while incorporating a redox-isomerization step. This approach provides an ideal platform to rapidly transform simple starting materials into complex amines.1 Introduction1.1 General Remarks1.2 Overview1.3 Scope of This Review2 Aromatization of Cyclic Amines2.1 Pyridines from Piperidine2.2 Isoquinolines from Tetrahydroisoquinolines and Quinolines from Tetrahydroquinolines2.3 Pyrroles from 3-Pyrroline or Pyrrolidine2.4 Indoles from Indolines3 Pericyclic Reactions3.1 (3+2)-Dipolar Cycloadditions3.2 6π-Electrocyclizations3.3 1,5-Proton Shifts4 Redox-Variants of Classic Transformations Incorporating a C–H Bond Functionalization Step4.1 α-Cyanation4.2 α-Alkynylation4.3 α-Phosphonation4.4 α-Arylation4.5 α-Alkylation with Ketones4.6 Redox-Ugi Reaction4.7 Miscellaneous Intermolecular Reactions5 Redox-Annulations6 Reactions Involving β-C–H Bond Functionalization7 Outlook
Keywords: C–H bond functionalization; amines; heterocycles; redox-neutral; redox-isomerization; condensation